Trends of Diabetic Retinopathy Research from 2018-2022: A bibliometric analysis: Poster Presentation - Observational Study - General practitioner - Aulia, Ariadne (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Diabetic Retinopathy (DR) is one of the leading cause of visual impairment and blindness. Abundant studies have been done around the topic. This study aims to identify research hotspot of DR during the last five years. Methods : Document search in the Scopus database was done using the term “diabetic retinopathy” in Title, Abstracts, and Author Keywords. We included only articles written in English published between 2018 and 2022. The dataset were analyzed using VOSviewer to conduct bibliometric analysis, such as citation analysis of sources and institutions, co-authorship analysis of countries, and co- occurrence analysis of author keywords. Results : A total of 8.377 articles on DR were retrieved. Number of articles in DR had been increasing steadily overtime. China had the most publications with over 2.000 articles, while United States had the most international collaboration. The most active institution was Guangdong Provincial Clinical Research Center for Ocular Diseases. Scientific Reports was the most prolific journal in DR research. Co- occurrence analysis of author keywords formed 5 clusters; DR management, risk factors for DR, examination for DR, pathogenesis of DR, and diagnostic method for DR. Conclusion : This study revealed research trends on diabetic retinopathy research for the last five years. It may provide information for researchers to identify potential collaborator and give better insight on DR research topics